Coating dog kibble with a commercial liquid acidifier reduces the risk of Salmonella cross-contamination - Huss, A. R.; Deliephan, A.; Fuller, J. C.; Jones, Cassandra K. (My University, 2017)
In recent years, several pet food recalls have been attributed to Salmonella contamination. In addition to the negative impacts on animal health, pet foods contaminated with Salmonella have been linked to infection in humans. To help reduce the risks to humans, the Food and Drug Administration has set forth a zero-tolerance policy for Salmonella in pet foods. Typically, the preconditioner and extruder operate at sufficient temperatures to destroy pathogenic bacteria. However, there is the potential for post-processing cross-contamination to adulterate the product. One potential method to reduce the risk of Salmonella cross-contamination in pet foods is through the addition of chemical additive coatings. The objective of this research was to evaluate the ability of the liquid acid, ?-hydroxy-?-methylbutyric acid (HMB; Metabolic Technologies Inc, Ames, IA), to reduce cross-contamination of dry extruded dog kibble with Salmonella. Liquid HMB was applied to a single formula of dog kibble at inclusion levels of 0, 0.9 and 1.5% (w:w) using a laboratory-scale mixer. The coated kibbles were then inoculated with Salmonella enterica subsp. enterica Serovar Enteritidis (ATCC 13076), grown in trypticase soy broth (TSB). Inoculated kibbles were enumerated for Salmonella on d 0, 1, 2, 7, and 14 post-inoculation. For enumerations, a subsample was collected, serial diluted and spread plated to Xylose Lysine Deoxycholate (XLD) agar. All inoculated plates were incubated at 37°C for 24 h, after which black colonies, typical for Salmonella, were counted and cfu/g calculated. The effects of HMB concentration, enumeration day and their interaction were all significant (P < 0.0001) on the resulting Salmonella concentration. Salmonella counts from Day 0 were 6.99, 5.59, and 4.88 log10 cfu/g for 0, 0.9 and 1.5% HMB, respectively. For HMB levels of 0.9 and 1.5%, counts were below the detectable limit for d 1, 2, 7, and 14. For 0% HMB, the Salmonella counts were found to decrease over time to 4.80, 3.99, 2.80, and 3.14 log10 cfu/g for d 1, 2, 7, and 14, respectively. Overall, the HMB coating was effective at reducing Salmonella artificially inoculated to dog kibbles. Further research is warranted to evaluate the minimum effective dose of HMB to reduce Salmonella in dog and cat kibbles.
Citation: Huss, A. R., Deliephan, A., Fuller, J. C., & Jones, C. K. (2016). Coating dog kibble with a commercial liquid acidifier reduces the risk of Salmonella cross-contamination. Journal of Animal Science, 94, 102-102. doi:10.2527/msasas2016-216
Keywords: Salmonella; Cross-Contamination; Petfood; Agriculture